PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN PERBANKAN DI KOTA MEDAN - Warsani P Sari; Linda Lores; Zainal Abidin (Universitas Islam Negeri Sumatera Utara, 2015)
This study aims to determine whether the characteristics of the company (company size, profitability, profile, board size and financial leverage), affect the disclosure of corporate social responsibility of the banking company in the city of Medan. Data analysis methods used in the study is a statistical analysis (multiple linear regression) using software (SPSS for Windows V15). To know the results of regression estimation is completely free of symptoms heteroskedastisitas, multikolionieritas and auto correlation, the authors do normality test, multicollinearity, heteroscedasticity test and test auto correlation test. To test the hypothesis, the authors used the coefficient of determination (R2), multiple regression analysis, partial test (t-test) and a simultaneous test (F-test). The results showed only the size of companies that have a significant influence on the disclosure of corporate social responsibility, while the level of profitability, corporate profile, board size, the level of financial leverage do not have a significant effect on the disclosure of corporate social responsibility.